2019
DOI: 10.3390/microorganisms7090309
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Ocular Surface Fungal Microbiome in Fungal Keratitis Patients

Abstract: Keratitis, an inflammatory disease of the eye, when neglected could lead to sight-threatening complications and ultimately blindness. Globally, over a million people are affected by keratitis annually. Keratitis has a microbial etiology and is caused by bacteria, fungi, viruses, etc. The present study compared the ocular surface fungal microbiome of healthy individuals and individuals with fungal keratitis. Fungal microbiomes from the conjunctival swabs of healthy individuals and from conjunctival swabs and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 50 publications
(73 reference statements)
3
47
1
Order By: Relevance
“…Studies based on 16S RNA sequencing and traditional culture methods have found that human OSs are colonized by a wide variety of microorganisms. Although recent studies have investigated the composition and changes in conjunctival microbiome profiles of individuals with fungal keratitis and bacterial keratitis, 12,13 a comprehensive study of OS microbiome changes associated with keratitis using shotgun metagenomics is lacking. Whether the ocular microbiome is associated with OS infections also remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies based on 16S RNA sequencing and traditional culture methods have found that human OSs are colonized by a wide variety of microorganisms. Although recent studies have investigated the composition and changes in conjunctival microbiome profiles of individuals with fungal keratitis and bacterial keratitis, 12,13 a comprehensive study of OS microbiome changes associated with keratitis using shotgun metagenomics is lacking. Whether the ocular microbiome is associated with OS infections also remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although the composition of the ocular microbiome is still under dispute, data have become available to indicate the distribution characteristics of OS microbial communities in health and disease states. Recent studies have demonstrated the potential relationship between changes in the OS microbiome and some conditions, such as trachoma, 11 fungal keratitis, 12,13 ulcerative bacterial keratitis, 14 conjunctivitis, 15 dry eye, 16 mesangial gland dysfunction, 17,18 blepharitis, 19 and contact lens wearing. 20,21 However, all of these studies were based on 16S rRNA gene sequencing, which, despite contributing to understanding the potential diversity of the OS bacterial flora, has limited ability to characterize nonbacterial components and functional profiles of the OS microbiome.…”
mentioning
confidence: 99%
“…Therefore analysis of the ocular surface mycobiome from all the participants may be required for comparison with vitreous. Since in the present study the ocular surface samples were not collected, the data of the present study was compared with the ocular surface mycobiome from published literature [9][10][11]. The mycobiome from blood in control and PFR group participants could have enhanced the understanding of the mycobiome penetration into the eye.…”
Section: Plos Onementioning
confidence: 99%
“…Negative correlations between OTUs occur is all groups at time T1, but they are remarkably more frequent in both selection regimes within the skin microbiome networks. In many studies, the increase of negative correlations in networks was associated to microbiota dysbiosis in several contexts of human lung infectious diseases [63][64][65], in dog's gut (Vázquez-Baeza et al 2016) and macaque model of tuberculosis for instance. Furthermore, network connectivity under stress was maintained by rare OTUs, while abundant OTUs were mainly composed of opportunistic invaders such as Mycoplasma and other genera related to sh pathogens like Aeromonas, Pseudomonas and Flavobacterium [66,67].…”
Section: Discussionmentioning
confidence: 99%